Decision Making and the Will of God A Biblical Alternative to the Traditional View - Friesen, Garry; Maxson, J. Robin (Portland Multnomah Press, 1980)
Instead of wondering, "How do I find the will of God?" a better question to pursue is, "How do I make good decisions?" Answering that question stands as the central purpose of this book. While the author challenges the traditional Christian approach to
Includes indexes.
Keywords: God (Christianity) -- Will. Decision making -- Moral and ethical aspects. Christian life